Heaven's a lie : a novel - Stroby, Wallace (Mulholland Books, 2021)
Joette Harper's life brings new meaning to the phrase "paycheck to paycheck." Struggling to afford her mother's sky-high medical bills and also keep the lights on in her trailer home, Joette needs a break. So, when she spies a bag full of money amongst the wreckage of a fiery car accident, she knows she can't just let it be. Inside is a bounty better than she could have dreamed--just shy of $300,000 in neatly stacked hundreds and fifties. Enough to pay off her debts, give her mother the care she deserves, and maybe even help out a few of her friends. But, of course, the missing briefcase didn't go unnoticed by its original owner, Travis Clay--a ruthless dealer who'll stop at nothing to get back what's his.